An ANALYSIS OF LOCAL CULTURE REPRESENTATION IN ENGLISH TEXTBOOKS FOR JUNIOR HIGH SCHOOL STUDENTS IN INDONESIA - Farrahillah, An-Nida (Critical Review of English-Arabic World Journal, 2023)
Incorporating local culture into textbooks is crucial for English language learning. This study aimed to analyze how local culture was represented in English textbooks for 9th-grade of junior high school students in Indonesia. The analysis focused on both textual and visual representations of cultural aspects, employing Yuen's (2011) framework, which identified products, practices, perspectives, and persons. This study utilized interpretive content analysis as a research method, encompassing the data analysis phases of preparation, organization, and reporting. Results showed that the textbooks successfully portray all four cultural aspects, with products being the predominant aspect. Additionally, religions emerged as a new aspect which was not specifically addressed in Yuen's previous study; however, during the analysis, they were depicted multiple times in the textbooks. Nevertheless, notable significant variations in the amount and types of data for each cultural aspect highlighted the necessity for a more balanced and comprehensive representation of culture in textbooks.